Is acute kidney injury a harbinger for chronic kidney disease? - Selewski, David T; Hyatt, Dylan M; Bennett, Kevin M; Charlton, Jennifer R (Current opinion in pediatrics, 2018)
Despite abundant evidence in adults, the relationship between acute kidney injury (AKI) and chronic kidney disease (CKD) remains unanswered in pediatrics. Obstacles to overcome include the challenges defining these entities and the lack of long-term follow-up studies. This review focuses on pediatric populations at high-risk for AKI, the evidence of the long-term effect of AKI on renal health, and biomarkers to detect renal disease. AKI in critically ill children and neonates is common and independently associated with adverse outcomes. Patients with diabetes and sickle cell disease along with neonates with necrotizing enterocolitis have been identified as high-risk for AKI. Preterm birth and neonates with AKI have signs of renal dysfunction early in childhood. Urinary biomarkers may identify AKI and CKD earlier than traditional biomarkers, but more work is necessary to determine their clinical utility. Promising technological advances including the ability to determine nephron number noninvasively will expand our ability to characterize the AKI to CKD transition. AKI is common and associated with poor outcomes. It is probable that AKI is a harbinger to CKD in pediatric populations. However, we currently lack the tools to definitely answer this question and more research is needed.